The Impact of Private Precautions on Home Burglary and Robbery in Brazil - Oliveira, Cristiano Aguiar de (Journal of quantitative criminology, 2018)
This study evaluates the effects of precaution technologies (i.e., window bars, extra locks, alarms and electric fences, CCTV, private security, dogs and combinations of these tools) on household burglary and robbery in Brazil.